PENGARUH PERSEPSI AUDITOR PEMERINTAH ATAS INDEPENDENSI, INTEGRITAS, DAN PROFESIONALISME TERHADAP KUALITAS HASIL PEMERIKSAAN - Priyadinata, Laksandi Eko; Rahman, Aulia Fuad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The Audit Report is a communication tool for financial statement‟susers on its suitability with general standard and criteria. In order to obtainUnqualified opinion, one entity (auditee) enables to do what it takes,including fraud if necessary. Using multiple regression analysis, this researchtests how the independency, integrity and professionalism affect to the quality ofAudit Report. The objects of the research are The Audit Board of The Republicof Indonesia, East Java Representatives.This research is an empirical research using purpose sampling to gainthe data. The respondents are auditors from The Audit Board of The Republic ofIndonesia, East Java Representatives. There are four variables in thisresearch, which are three independent of them (independence, integrity, andprofessionalism) and one dependent variable (Quality of Audit Report).It can be concluded from this research that government auditors perceptionof independency, integrity and professionalism significantly affect to the AuditReport’s quality. Determination coefficient value shows that independency,integrity, and professionalism, altogether affect dependent variable (audi tr epor t qual i t y ) for 56,50%, while the rest 43,50% are affected by otherfactors.Keywords: Independency, Integrity, Professionalism, and Quality of Audit Report.